ANALISA KINERJA KEUANGAN KOPERASI DI KUD SUMBER MAKMUR NGANTANG MALANG - Sudjoni, Moch. Noerhadi; Saputro, Arief Joko (Universitas Wahid Hasyim, 2024)
Financial health performance will determine the progress of the cooperative. The healthier the financial performance, the more advanced and independent the cooperative will be. For this reason, it is necessary to analyze the performance of the financial reports, so that management can make the right decisions for the further development of the cooperative. The success of a cooperative will reflect the qualifications or quality of its financial health performance. The aim of this research is to determine the health performance of the financial reports of KUD Sumber Makmur Ngantang. This research method uses a case study approach. The data collection method is using primary data and secondary data. The research location is KUD Sumber Makmur Ngantang District. Poor. The financial performance analysis period is the balance sheet & profit and loss report for 2021 & 2022. This research uses the